Humic substances and their effects on the micropropagation of banana (Research, Society and Development, 2021)
The growing concern to promote sustainable agriculture, seeking environmental preservation and, at the same time, increased productivity resulted in the search for technologies for the implementation of agricultural production systems, with ecological approaches and responsible use of natural resources, in the economic, political and social contexts in each region. One of the potential alternatives to achieve these results would be the use of humic substances, considering their direct and indirect mechanisms aimed at increasing agricultural production. Thus, the objective of this work was to evaluate the bioactivity of humic and fulvic acids, as well as to promote improvements in the phytotechnical attributes of banana cv. Prata-Anã micropropagated. The treatments consisted of five doses of humic acid and fulvic acid (2; 5; 10; 20 and 40 mg L-1) and a control without humic substances. Higher values ​​for the length of the aerial part and the larger root were obtained with the use of 40 mg L-1 fulvic acid. The results prove the ability of fulvic acid to improve the in vitro development of banana explants.